2017
DOI: 10.5999/aps.2017.44.5.390
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Koreans’ Perceptions of Facial Beauty

Abstract: BackgroundThis article aims to investigate current perceptions of beauty of the general public and physicians without a specialization in plastic surgery performing aesthetic procedures.MethodsA cross-sectional and interviewing questionnaire was administered to 290 people in Seoul, South Korea in September 2015. The questionnaire addressed three issues: general attitudes about plastic surgery (Q1), perception of and preferences regarding Korean female celebrities’ facial attractiveness (Q2), and the relative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…For female beauty, respondents preferred smooth skin around the eyes, which may increase the likelihood of women considering periorbital aesthetic medical procedures. This is consistent with findings from studies in Europe and Asia where eyes, along with skin, were commonly regarded as important for facial attractiveness 11,12,13. It is interesting that eyes and smile were also featured that most respondents thought were their most beautiful facial feature.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For female beauty, respondents preferred smooth skin around the eyes, which may increase the likelihood of women considering periorbital aesthetic medical procedures. This is consistent with findings from studies in Europe and Asia where eyes, along with skin, were commonly regarded as important for facial attractiveness 11,12,13. It is interesting that eyes and smile were also featured that most respondents thought were their most beautiful facial feature.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with findings from studies in Europe and Asia where eyes, along with skin, were commonly regarded as important for facial attractiveness. [11][12][13] It is interesting that eyes and smile were also featured that most respondents thought were their most beautiful facial feature.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our survey revealed that South Indian Dravidian women considered an oval face with straight facial profile, straight nose, narrow chin, well-defined lips, arched brow with obtuse jawline to be the most attractive. This is in alignment with findings from similar surveys done in other Asian ethnicities [14,15,22]. And it can be agreed that multicultural perception of beauty is more unified than diverse.…”
Section: Discussionsupporting
confidence: 87%
“…According to the Global Survey Results of 2018 released by International Society of Aesthetic Plastic Surgery (ISAPS) and American Society of Plastic surgeons (ASPS), the rave for cosmetic correction of the face is only on the rise with more people wanting to look beautiful and young [13]. Hence, it becomes prudent for the cosmetic surgeon to not only cater to the ideal set standards of beauty but also to the actual needs and desires of the patients [14]. That being said, though the concept of beauty is now universal, certain cultural nuances do exist and is of respectable importance when aesthetic facial correction is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Literature describing standards of beauty across the Middle East is relatively scarce, compared with those for white, Asian, and African populations. 410 The region is characterized by a wide range of ethnic and racial diversity, even within individual countries. What has been published rarely covers more than one Middle Eastern country or ethnic group.…”
Section: Introductionmentioning
confidence: 99%